Cellulose of Trichoderma viride for Biological Degradation of Cellulosic Wastes - R. Khan, Mohammad; Amin, Farzana (Asian Journal of Chemistry, 2012)
Microbial cellulase is under intensive investigation due to its expected use as a tool for biological degradation of cellulosic wastes. The production of cellulase by Trichoderma viride in 5 % wheat bran medium with glucose as the carbon source was studied. The work was extended to investigate the biological degradation of cellulosic wastes such as banana stem, waste newspaper, waste plane paper, etc., during the growth of the organism due to the production of the cellulase activity. The results indicated that the organism produced two cellulases, one in the earlier phase and the second in the later phase. The cellulase produced in the earlier phase was in significant quantity and was subject to induction by the cellulosic substrates included in the medium. The banana stems, particularly, in the shredded form underwent a large degradation, as this material after inclusion in the medium, underwent 90 % loss in weight. The results will hopefully help the world in production of sugar and ethanol from no-cost solid wastes and will offer partial solution to the ongoing food and energy crises along with an effective disposal of solid waste to keep environment clean.